2021
DOI: 10.3390/ijerph18136828
|View full text |Cite
|
Sign up to set email alerts
|

An Umbrella Review of the Work and Health Impacts of Working in an Epidemic/Pandemic Environment

Abstract: This umbrella review of reviews examined the evidence on the work and health impacts of working in an epidemic/pandemic environment, factors associated with these impacts, and risk mitigation or intervention strategies that address these factors. We examined review articles published in MEDLINE, PsycINFO and Embase between 2000 and 2020. Data extracted from the included reviews were analyzed using a narrative synthesis. The search yielded 1524 unique citations, of which 31 were included. Included studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
2
3
0
Order By: Relevance
“…With regard to our first research question concerning the levels of stress and symptoms of anxiety and depression nurses experienced, our findings showed that nurses who provided direct patient care during the COVID-19 pandemic in the Canary Islands, Spain, reported a considerable prevalence of perceived stress and symptoms of anxiety and depression. These results were in line with recent studies that revealed that the prevalence of anxiety and depression disorders was relatively high among healthcare workers during the COVID-19 pandemic [ 11 , 33 , 34 , 35 ]. Our results confirmed our first hypothesis, which posited that nurses’ perceived stress was positively correlated with symptoms of anxiety and depression.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to our first research question concerning the levels of stress and symptoms of anxiety and depression nurses experienced, our findings showed that nurses who provided direct patient care during the COVID-19 pandemic in the Canary Islands, Spain, reported a considerable prevalence of perceived stress and symptoms of anxiety and depression. These results were in line with recent studies that revealed that the prevalence of anxiety and depression disorders was relatively high among healthcare workers during the COVID-19 pandemic [ 11 , 33 , 34 , 35 ]. Our results confirmed our first hypothesis, which posited that nurses’ perceived stress was positively correlated with symptoms of anxiety and depression.…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, this is the first systematic review of studies describing the impact of healthcare epidemics and pandemics (COVID-19, MERS, and SARS) on the work environment and employee health, and the effect of interventions, including industries within and outside healthcare organizations. Previous reviews have reported healthcare to be the most thoroughly studied industry [ 5 , 9 ] and the present review confirms this is still the case.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, there is a need to systematically review the current research on how corona epidemics and pandemics impacted working life and employee health, and what measures aimed at counteracting negative health effects on employees were effective. Several reviews of the work environment during the COVID-19 pandemic have been published [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. However, most reviews focused solely on the impact on healthcare organizations [ 6 , 7 , 8 , 10 , 11 , 12 ], and it is important to include studies describing other labor market industries and how they are affected by epidemics and pandemics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have outlined several severe health-related consequences of fear of COVID-19 in particular for healthcare workers. 14,15 However, we argue that these studies take a somewhat healthcare-biased perspective, 16 which makes it difficult to transfer knowledge to other occupations since healthcare professionals are more familiar with disease prevention in the context of their job unlike ECPs. Most studies were conducted with small samples during initial stages of the COVID-19 pandemic (including lockdown periods), which can be seen as a general limitation.…”
mentioning
confidence: 99%